Assessment of arrangements for the detection of radon emanating from soil - Papachristodoulou, C. A.; Ioannides, K. G.; Mertzimekis, T. J.; Karamanis, D. T.; Stamoulis, K. C. (HNPS Advances in Nuclear Physics, 2020)
CR-39 solid state nuclear track detectors were used to measure radon (222Rn) concentration in the soil near ground surface. The measurements were performed in the campus of the University of Ioannina, using PVC tubes at 0.25 m intervals down to depths of 1.25 m. The track detectors were etched in 7N NaOH solutions at 80°C. The tracks were counted using a microscope - camera - computer system, developed for automatic counting. The results provide evidence for the non-diffusive transport of radon in soils. A transport length of (46.9 ± 3.2) cm was estimated for radon transport near ground surface. Also the variation of soil's radon was correlated to meteorological variations.